ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA YANG MENGGUNAKAN MODEL PEMBELAJARAN RECIPROCAL TEACHING - Mega Fitria; Bana Kartasasmita; In In Supianti (Universitas Suryakancana, 2019)
The process of student understanding of mathematical concepts is still low, this happens to most students at SMP Nasional Bandung. Students and students experience obstacles in learning and understanding mathematical concepts, especially when the material provided is changed to different problems. One of the reasons students find it difficult to understand mathematical concepts is the use of conventional learning models. Therefore, the use of the Reciprocal Teaching learning model using experimental research methods is expected to make it easier for students to understand mathematical concepts, especially when the material provided is changed into various forms. Class VII students at SMP Nasional Bandung became the population in the study, while the sample was class VII-A and VII-E students who were randomly selected. The test used is the type of description as an instrument and will be tested on class VIIIA. After the analysis is carried out, produce the feasibility of all test questions worthy of being used in research. Analysis of the trial data is carried out using a t-test using the SPSS 23.0 (Independent Sample T-Test) application. The conclusion is the use of the Reciprocal Teaching learning model can improve the ability of students to understand mathematical concepts compared to conventional learning models. Therefore, the use of the Reciprocal Teaching learning model becomes an alternative for teachers when learning about students so that learning becomes more effective, active and enjoyable.Keywords: Mathematical Concept Understanding, Reciprocal Teaching, Mathematical Proficiency